STUDENT LEARNING OUTCOMES: IN TERMS OF EMOCIAL INTELLIGENCE AND SELF-MANAGEMENT SKILLS - Nurhidayah, Nurhidayah (JIWA: Jurnal Psikologi Indonesia, 2024)
The purpose of this study was to determine the effect of emotional quotient and self management ability on mathematics learning outcomes of students of SMPN 5 Wonomulyo. This study is an ex-post facto causal study with a sample of 44 students. Data collection techniques used the following instruments: (1) emotional quotient questionnaire, (2) learning self management ability, and (3) mathematics learning outcomes test. Data analysis using descriptive statistics and inferential analysis. The results of the descriptive test of the data show that: (1) emotional quotient is in the high category, (2) self management ability is in good category, and (3) mathematics learning outcomes are in the high category. The results of analysis testing using simple linear regression analysis and multiple linear regression show that: (1) emotional quotient has effect on students mathematics learning outcomes, (2) self management ability has effect on students mathematics learning outcomes, and (3) emotional quotient and learning styles have no effect on students mathematics learning outcomes.